2017
DOI: 10.4274/turkderm.23169
|View full text |Cite
|
Sign up to set email alerts
|

Resistance status of antibiotics in Gram-positive bacteria isolated from acne lesions in İstanbul

Abstract: Background and Design: Acne vulgaris is a multifactorial disease in which Propionibacterium acnes is thought to play an important role in the pathogenesis of inflamed lesions. There is also significant in vitro evidence suggesting a possible pathogenetic role for Staphylococci in acne vulgaris and an in vitro study of patients who were undergoing evaluation for acne, showed that 53% of participants were colonised with Staphylococcus epidermidis. Materials and Methods: In this study, 29 P. acnes isolates and 61… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…When the effectiveness of Nadifloxacin, Erythromycin, Clindamycin, and Tetracycline against P. acnes and CNS isolates from inflammatory lesions were compared, the MIC for Nadifloxacin was ≤1 µg/mL and resistance was shown at MIC level ≥4 µg/mL. [58] Compared to Ciprofloxacin, Erythromycin, and Clindamycin, Nadifloxacin demonstrated better activity against P. acnes as the MIC50 and MIC90 values were lesser compared to those of other antimicrobials. [45] Biswal et al (2016) demonstrated that the MIC50 and MIC90 values for Nadifloxacin (0.25 and 1µg/ mL) were lower than those for Ciprofloxacin (0.5 and 1µg/ mL).…”
Section: • Adapalene+nf • Adapalene Monotherapymentioning
confidence: 98%
“…When the effectiveness of Nadifloxacin, Erythromycin, Clindamycin, and Tetracycline against P. acnes and CNS isolates from inflammatory lesions were compared, the MIC for Nadifloxacin was ≤1 µg/mL and resistance was shown at MIC level ≥4 µg/mL. [58] Compared to Ciprofloxacin, Erythromycin, and Clindamycin, Nadifloxacin demonstrated better activity against P. acnes as the MIC50 and MIC90 values were lesser compared to those of other antimicrobials. [45] Biswal et al (2016) demonstrated that the MIC50 and MIC90 values for Nadifloxacin (0.25 and 1µg/ mL) were lower than those for Ciprofloxacin (0.5 and 1µg/ mL).…”
Section: • Adapalene+nf • Adapalene Monotherapymentioning
confidence: 98%